Modifications induced by acetylacetone in properties of sol-gel derived Y3Al5O12:Tb3+ - I: Structural and morphological organizations - Potdevin, Audrey; Chadeyron, Geneviève; Briois, Valérie; Leroux, Fabrice; Santilli, Celso Valentim [UNESP]; Dubois, Marc; Boyer, Damien; Mahiou, Rachid (Royal Society of Chemistry (RSC), 2010)
Acetylacetone has been used as a chemical modifier for the synthesis of undoped and Tb3+-doped Y3Al5O12 powders. A systematic investigation concerning its influence on the structural and morphological properties of amorphous and crystallized samples has been carried out. These properties have been comparatively studied by means of X-ray diffraction, infrared spectroscopy, SEM, XAS and SAXS. 27Al NMR and EPR experiments have been performed to complete the study. The combined results have evidenced that acetylacetone promotes organic groups departure during calcination, entailing a better structural organization at lower temperatures compared with unmodified powders. Structuration has been proven to occur at short-scale range until a 600°C heating treatment before being extended by coalescence at higher temperatures. Finally, the presence of acac ligands on the alkoxides leads to a monomer-cluster aggregation process, and thus to a more open network. © 2010 The Royal Society of Chemistry.
Keywords: Acetylacetone; Alkoxides; Chemical modifiers; Cluster aggregation; Heating treatments; Higher temperatures; Open network; Organic group; SEM; Structural and morphological properties; Structural organization; Structuration; Systematic investigations; Agglomeration; Aluminum; Calcination; Coalescence; Gels; Infrared spectroscopy; Powders; Synthesis (chemical); Terbium alloys; X ray diffraction; Acetone